Case Studies in Spatial Point Process Modeling
DOI: 10.1007/0-387-31144-0_2
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Spatial Point Patterns in R

Abstract: Summary. We describe practical techniques for fitting stochastic models to spatial point pattern data in the statistical package R. The techniques have been implemented in our package spatstat in R. They are demonstrated on two example datasets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
225
0
6

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(271 citation statements)
references
References 65 publications
0
225
0
6
Order By: Relevance
“…The Ripley's L Function for multi-distance spatial cluster analysis was also applied. [20][21][22] All analyses were performed in R. 23 …”
Section: Methodsmentioning
confidence: 99%
“…The Ripley's L Function for multi-distance spatial cluster analysis was also applied. [20][21][22] All analyses were performed in R. 23 …”
Section: Methodsmentioning
confidence: 99%
“…For each species, we fitted heterogeneous Poisson models with the intensity function estimated as a log-linear function of second order polynomials of spatial coordinates x and y (Baddeley and Turner, 2006;De la Cruz, 2006;Liu et al 2007). This results in a nonstationary intensity function that accounts for the underlying spatial trend of each species, allowing the inhomogeneous K function to correctly estimate second order spatial dependencies.…”
Section: P2mentioning
confidence: 99%
“…We find that GA is correlated with the spectral parameter η (Madgwick et al 2002), an indicator of the star formation rate of galaxies. Observations indicate that the lower star formation rate of group galaxies is visible out to 2R 200 (Balogh et al 1998), while ΛCDM numerical simulations show that particles that penetrate deep into dark matter halos travel out to 2.6R 200 (Gill et al 2005). In this work, we have found that galaxies represent two statistically distinct groups with a transition at η = −1.4 and d c = 1.5R 200 , a scale somewhat smaller (by 25%) than the observed radius for decreased star formation, but consistent with this value.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we estimate K using the library spatstat (see Baddeley 2008) within the R statistical package. The command Kmeasure (spatstat) executes the following steps:…”
Section: Probing Anisotropy Around Groupsmentioning
confidence: 99%